2016
DOI: 10.1016/j.jcrysgro.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 6.1 Å III–V materials grown on GaAs and Si: A comparison of GaSb/GaAs epitaxy and GaSb/AlSb/Si epitaxy

Abstract: GaSb p-in photodiodes were grown on GaAs and Si, using interfacial misfit arrays, and on native GaSb. For the samples grown on GaAs and Si, high-resolution transmission electron microscopy images revealed interface atomic periodicities in agreement with atomistic modeling. Surface defect densities of ~1 × 10 8 cm −2 were measured for both samples. Atomic force microscopy scans revealed surface roughnesses of around 1.6 nm, compared with 0.5 nm for the sample grown on native GaSb. Dark current and spectral resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…3(b)). This can be attributed to the threading dislocations in agreement with previous reports for GaSb grown on Si [20]. The small peak on the left side of the InAsSb LED peak is attributed to the AlAsSb barrier.…”
Section: Resultssupporting
confidence: 91%
“…3(b)). This can be attributed to the threading dislocations in agreement with previous reports for GaSb grown on Si [20]. The small peak on the left side of the InAsSb LED peak is attributed to the AlAsSb barrier.…”
Section: Resultssupporting
confidence: 91%
“…After the growth of a further GaAs buffer layer of 10 nm, the As source was shut for 1 minute to minimise the As background, followed by a 10 s growth interrupt to desorb the As surface layer from the sample. This was in preparation for the growth of the GaSb via the interface misfit method 30 , needed for the transition to the ~6.1 Å lattice constant of the active layers of the device. Following the initial introduction of Sb 2 flux from a valved cracker source, the substrate temperature was decreased to 500 °C and a 630-nm-thick GaSb layer was grown.…”
Section: Methodsmentioning
confidence: 99%
“…We want to emphasize the fact that our 5 μm thick GaSb on the Si sample (3 μm GaSb buffer + 2 μm InGaSb/GaSb MQW LED epi structure) has a TDD lower than the lowest TDD reported previously. Table lists the GaSb buffer structures on Si and TDD values of previous results from other groups. ,,,,,, Interestingly, other authors from refs and reported that use of SLS is effective in reducing TDD. We believe that it is due to the different SLS structure.…”
Section: Resultsmentioning
confidence: 93%
“…Table 2 lists the GaSb buffer structures on Si and TDD values of previous results from other groups. 7,9,20,21,27,28,34 Interestingly, other authors from refs 9 and 21 reported that use of SLS is effective in reducing TDD. We believe that it is due to the different SLS structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%